Modeling geared turbofan and open rotor engine performance for year-2050 long-range and short-range aircraft - Mastropierro, Francesco Saverio; Sebastiampillai, Joshua; Jacob, Florian; Rolt, Andrew Martin (ASME, 2019)
The paper provides design and performance data for two envisaged year-2050 engines: a geared high bypass turbofan for intercontinental missions and a contra-rotating pusher open rotor targeting short to medium range aircraft. It defines component performance and cycle parameters, general arrangements, sizes and weights. Reduced thrust requirements reflect expected improvements in engine and airframe technologies. Advanced simulation platforms have been developed to model the engines and details of individual components. The engines are optimised and compared with 'baseline' year-2000 turbofans and an anticipated year-2025 open rotor to quantify the relative fuel-burn benefits. A preliminary scaling with year-2050 'reference' engines, highlights trade-offs between reduced specific fuel consumption (SFC) and increased engine weight and diameter. These parameters are converted into mission fuel burn variations using linear and non-linear trade factors. The final turbofan has an optimised design-point bypass ratio of 16.8, and a maximum overall pressure ratio of 75.4, for a 31.5% TOC thrust reduction and a 46% mission fuel burn reduction per passenger kilometre compared to the respective 'baseline' engine-aircraft combination. The open rotor SFC is 9.5% less than the year-2025 open rotor and 39% less than the year-2000 turbofan, while the TOC thrust increases by 8% versus the 2025 open rotor, due to assumed increase in passenger capacity. Combined with airframe improvements, the final open rotor-powered aircraft has a 59% fuel-burn reduction per passenger kilometre relative to its baseline.
Keywords: Tradeoffs; Weight (Mass); Simulation; Fuel consumption; Turbofans; Rotors; Modeling; Aircraft; Engines; Pressure